PERANCANGAN SISTEM KENDALI HEXACOPTER MENGGUNAKAN FUZZY LOGIC CONTROL - Al, Al; Saputra, Arifwindi; Premadi, Aswir; Effendi, Asnal; Dasman, Dasman (Jurnal Teknologi dan Vokasi, 2025)
The development of hexacopters has progressed significantly in both hardware and software, leading to increased complexity. Despite these advancements, several challenges remain. The nonlinear, multivariable, and dynamic nature of hexacopter systems often results in flight instability, suboptimal precision in movements, and reduced flight duration. To address these issues, this study proposes the implementation of a fuzzy logic control (FLC) system to enhance the performance and stability of hexacopters during flight. The control system aims to minimize rise time, settling time, and overshoot. The research methodology involves developing a mathematical model of the open-loop system using the System Identification Toolbox in MATLAB, optimizing PID values through the PID Tuner, and designing the fuzzy control system based on error and delta error. The open-loop system demonstrates performance metrics of rise time (Tr) 4.60 s, delay time (Td) 2.76 s, peak time (Tp) 6.50 s, settling time (Ts) 5.91 s, and overshoot (Mp) 1.29%. With PID control, the performance improves to rise time (Tr) 3.24 s, delay time (Td) 1.85 s, peak time (Tp) 10.00 s, settling time (Ts) 9.55 s, and overshoot (Mp) 0%. Furthermore, the fuzzy logic controller achieves superior results with rise time (Tr) 3.19 s, delay time (Td) 1.53 s, peak time (Tp) 4.64 s, settling time (Ts) 3.37 s, and overshoot (Mp) 0%.